Signal processing analysis of DSP based PWM generation for high switching frequency voltage source inverter. (1st October 2015) - Shah, Hardik A.; Shah, Satish K.; Patel, Rakesh M.
Abstract : This paper presents real time hardware implementation of DSP based 180 degree control algorithm and MATLAB SIMULINK based software Implementation for 3-phase 4-leg IGBT based voltage source inverter. Triggering pulses generated using Texas Instruments TMS 320F28335 DSP controller and that triggers the 6 IGBTs of Voltage source inverter. Results of pulse generated using DSP and output of the Voltage source inverter were captured using Digital Storage Oscilloscope. FFT analysis for output signal of software and hardware implementation presented with the analysis.